The three branches : A comparative model of separation of powers - Möllers, Christoph, 1969- (Oxford : Oxford University Press, 2013)
The idea of the separation of powers is still popular in much political and constitutional discourse, though its meaning for the modern state remains unclear and contested. This book develops an original account of the principle and its implications for modern national and transnational public bodies
II. The Internationalized Constitutional StateIII. European Integration; IV. International Law; Chapter 4 Separation of Powers Beyond the State; Informality; Governance; Constitutionalization; The Diffusion of Accountability; Freedom, Regime, and Fourth Power; Outlook Governance-Constitutionalization-Fourth Branches?; Bibliography; Index; Footnotes
Includes bibliographical references and index
Keywords: Separation of powers